Rough-fuzzy pattern recognition : applications in bioinformatics and medical imaging - Maji, Pradipta, 1976-; Pal, Sankar K. (Hoboken, N.J. : John Wiley & Sons, 2012)
'This book provides a unified framework describing how rough-fuzzy computing techniques can be formulated and used in building efficient pattern recognition models. Based on the existing as well as new results, the book is structured according to the major phases of a pattern recognition system (e.g., classification, clustering, and feature selection) with a balanced mixture of theory, algorithm and applications. Special emphasis has been given to applications in bioinformatics and medical image processing. The book is useful for graduate students and researchers in computer science, electrical engineering, system science, medical science, and information technology. Researchers and practitioners in industry and R&D laboratories will also benefit'--
'The proposed volume provides a unified framework describing how rough-fuzzy computing techniques can be judiciously formulated and used in building efficient pattern recognition models'--
Includes bibliographical references and index.
Keywords: Fuzzy systems in medicine; Pattern recognition systems; Bioinformatics; Diagnostic imaging -- Data processing